RE: GITR GENE DELETION AND GITR-FC SOLUBLE PROTEIN ADMINISTRATION INHIBIT MULTIPLE ORGAN FAILURE INDUCED BY ZYMOSAN. DOI: 10.1097/SHK.0B013E3182262C48 - Salvatore Cuzzocrea (Shock, 2024)
BACKGROUND: The Primary Sclerosing Cholangitis Symptom Assessment Project (PSC-SAP) is a research initiative aimed at developing regulatory-grade PSC-specific symptom measures. During the initial screening phase for PSC-SAP, patient-reported symptom data were collected from a cohort of symptomatic adults. The current study aims to comprehensively characterize a range of symptoms and identify predictors of symptom burden and mental and physical health-related quality of life (HRQOL). METHODS: Adults were primarily recruited through the PSC Partners Patient Registry for this cross-sectional study. Eligible participants completed a telephone-based survey that screened for 13 PSC-associated symptoms experienced in the last month and collected sociodemographic, clinical, and HRQOL scores using the PROMIS (Patient-Reported Outcomes Measurement Information System) global health measure. Multivariable linear regressions were used to model outcomes of total symptom burden and HRQOL. RESULTS: Among 126 symptomatic participants, 88% were White, 60% were female, and the mean age was 47 years. The most prevalent symptoms were fatigue (83%) and daytime drowsiness (73%), followed by >60% reporting anxiety, liver pain, brain fog, sleep disturbance, and pruritus. Female sex and cirrhosis were associated with higher symptom burden scores. Factors such as age, history of cholangitis attacks, and inflammatory bowel disease (IBD) were not. Adding a total symptom burden score to initial models substantially increased the explanation of variation in mental HRQOL (from 9% to 48%) and physical HRQOL (from 12% to 51%) scores. CONCLUSIONS: Among symptomatic adults living with PSC, 6 PSC symptoms emerged as highly prevalent. With total symptom burden strongly associated with mental and physical HRQOL, multisymptom assessments should be utilized in future HRQOL studies of PSC and may help improve clinical care for those suffering from PSC.